Representasi Gender dalam Kakawin Nītiśāstra - Putu Gede Suarya Natha (Pusat riset dan Inovasi Nasional, 2026)
Kakawin Nītiśāstra is a classic Old Javanese literary work that holds significant cultural value, especially within Balinese society, and is widely studied in academic settings. Previous research has primarily focused on its ethical teachings and character education, highlighting its role as a moral guide for life. However, a closer examination of the text reveals stanzas that portray women in ways that contradict this interpretation, specifically presenting them as unequal to men. This study addresses the gap in existing literature by focusing on gender representation in Kakawin Nītiśāstra. Given its portrayal as a